Inclusão digital - Parreira, Arthur Mortari [UNESP] (2015)
This Project aims to contribute to the digital inclusion of the population of Jaboticabal / SP, where is locate the Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP – FCAV). The target audience is students from public schools in the city, and we aim to acquaint, motivate and prepare them for meaningful use of computers and the internet. In addition to reflecting on the impact of these Technologies in a several aspects of life, society and their teaching, promoting digital education for this population’s group and make them able to enter at the labor market.